Left Atrial Function Post Radiofrequency and Cryoballoon Ablation Assessed by Volume-Pressure Loops - Karanasos, Antonios; Tyrovolas, Konstantinos; Tsiachris, Dimitrios; Efremidis, Michalis; Kordalis, Athanasios; Karmpalioti, Maria; Prappa, Efstathia; Karagiannis, Stefanos; Aggeli, Constantina; Gatzoulis, Konstantinos; Tousoulis, Dimitrios; Tsioufis, Costas; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Left atrial (LA) function is linked to atrial fibrillation (AF) pathogenesis. AF catheter ablation decreases disease burden with potentially favourable effects on cardiac function. Atrial volume-pressure loops can optimally assess LA function. Objective: To investigate changes in LA function by volume-pressure loops after paroxysmal AF ablation and explored potential differences between radiofrequency and cryoballoon ablation. Methods: We analysed 44 patients undergoing paroxysmal AF ablation from 2 centres, 22 treated with radiofrequency and 22 with cryoablation. Pre- and post-procedure, all patients underwent real-time three-dimensional transthoracic echocardiogram to evaluate LA volume, while simultaneously recording LA pressure following transseptal puncture. Volume-pressure loops pre- and post-procedure were created by paired data. Areas of A-loop (LA booster pump function) and V-loop (LA reservoir function), and the stiffness constant determining the slope of the exponential curve during LA filling were calculated. Results: Average LA pressure, A-wave and V-wave amplitude were increased post-procedurally (p<0.001). Overall, A-loop area decreased (p=0.001) and V-loop area tended to increase (p=0.07). The change in both A-loop and V-loop areas was similar between radiofrequency- and cryoballoon-treated patients (p=0.18 and p=0.52, respectively). However, compared to cryoballoon-treated patients, radiofrequency-treated patients had higher increase in the stiffness constant (b=0.059; 95%CI: 0.022-0.096;p=0.006). Conclusion: AF catheter ablation by radiofrequency or cryoballoon is associated with decrease of the booster pump function and increase of the reservoir function. Moreover, there is a post-procedural increase of LA pressure which is associated with acute increase in LA stiffness in radiofrequency ablation, but not in cryoablation.